Trifluoromethanesulfonic Acid as an Efficient Catalyst in the Reduction of Ketimines - Li, Jianhui; Wang, Zhouyu; Jiang, Zhenju; Jiang, Shengqian (Asian Journal of Chemistry, 2011)
Trifluoromethanesulfonic acid was found to be highly efficient catalyst in the reduction of ketimines with Hantzsh esters as the hydrogen source. The catalyst loading could be decreased to 1 mol %. Moderate to excellent isolated yields (up to 99 %) were obtained under mild conditions.